MAGNETIC MATERIALS FOR DATA STORAGE - M. Matsumoto (Jurnal Sains Materi Indonesia, 2003)
Required properties and design idea for magnetic data storage medium to attain high density recording are studied, followed by the descriptions of experimentally obtained properties of thin ﬁlms of Ba-ferrite,’ NdFeB, FePt, SmCo prospected for high density storage.